Optimization of production conditions, isolation, purification, and characterization of tannase from filamentous fungi - Thakur, Nisha; Nath, Amarjit K; Sharma, Amit (Folia microbiologica, 2024)
Tannase-producing filamentous fungi residing alongside tannin-rich ambient in the Northwest Himalayas were isolated at laboratory conditions and further identified by 18S ribosomal RNA gene sequencing. Five most potent tannase producing strains (EI ≥ 2.0), designated Aspergillus fumigatus AN1, Fusarium redolens AN2, Penicillium crustosum AN3, Penicillium restrictum AN4, and Penicillium commune AN5, were characterized. The strain Penicillium crustosum AN3 exhibited a maximum zone dia (25.66 mm ± 0.38). During solid-state fermentation, a maximal amount of tannase was attained with Penicillium crustosum AN3 using pine needles (substrate) by adopting response surface methodology for culture parameter optimization. Gel filtration chromatography yielded 46.48% of the partially purified enzyme with 3.94-fold of tannase purification. We found two subunits in enzyme-117.76 KDa and 88.51 KDa, respectively, in the SDS-PAGE. Furthermore, the characterization of partially purified tannase revealed a maximum enzyme activity of 8.36 U/mL at 30 °C using a substrate concentration (methyl gallate) of 10 mM. To broaden the knowledge of crude enzyme application, dye degradation studies were subjected to extracellular crude tannase from Penicillium crustosum AN3 where the maximum degradation achieved at a low enzyme concentration (5 ppm).
Keywords: Coloring Agents; karboxylesterhydrolasy; molekulová hmotnost; Fungi; Temperature; Solid-state fermentation; Culture Media; Enzyme Stability; kultivační média; fylogeneze; RNA, Ribosomal, 18S; Molecular Weight; Fungus; Pine needles; Phylogeny; Fungal Proteins; houby; fermentace; stabilita enzymů; substrátová specifita; Fusarium; Purification; barvicí látky; Substrate Specificity; Carboxylic Ester Hydrolases; Fermentation; teplota; RNA ribozomální 18S; Application; Tannase; Penicillium; fungální proteiny